EFFECT OF THE USE OF VERMICOMPOST AND RHIZOBIAL INOCULATION ON SOME SOIL CHARACTERISTICS, GROWTH AND YIELD OF MUNG BEAN Vigni radiate L. - & Mutlag, Alkobaisy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
A field experiment was conducted in silty loam soil to study the effect of vermicompost fertilizer and inoculums Rhizobium legumenosarum on growth and yield of mung bean (Vigni radiate L.), and some soil properties after planting. The experiment consists of nine treatments as follows :T1: control , T2: full recommended mineral fertilizer, T3: vermicompost 8 t.ha-1, T4: vermicompost 16 t.ha-1, T5: vermicompost 8 t.ha-1+ rhizobia, T6: vermicompost16 t.ha-1+ rhizobia, T7: vermicompost 2 t.ha-1+ ½ recommended mineral fertilizer, T8: rhizobia + ½ recommended mineral fertilizer, T9: vermicompost 8 t.ha-1 + rhizobia +½ recommended mineral fertilizer. The experiment was conducted according to RCBD design with three replications. The results were indicated that the use of vermicompost 16 t. ha-1 with the rhizobia inoculation (T6) has improved some soil properties, as this treatment reduced the pH and EC of the soil to 7.18 and 2.20 dsm-1. While CEC and O.M increased to 47.9 Cmole Kg-1 and 2.96%, respectively. Whereas, the treatment T9 was superior in most of the traits, including plant height (70.1 cm), Root weight (5.8 g plant-1) and a number of active and total root nodes (41.3 and 36.6 nodes plant -1). The treatment T9 also gave the best characteristics of the yield components, including the number of pods plant-1, weight of pods plant-1, weight 1000 seeds (g), total yield and was 51.0 pods plant-1, 92.4 g plant -1,49.8 g.plant-1, 1216.95 kg.ha-1 respectively.